Clinically Role of Serum Procalcitonin and C-reactive Protein Concentration in Diabetic Foot Ulcer Infections - Gahlot, Dr. Ghanshyam; Soni, Dr. Yogita; Vyas, Dr. R. K.; Agarwal, Dr. R. P. (International Journal of Innovative Research in Medical Science, 2017)
Aim: - Serum inflammatory markers, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), white blood cells (WBC), and procalcitonin (PCT), have been used for the diagnosis of foot infections in patients with diabetes. However, little is known about their changes during treatment of patients with foot infections. Procalcitonin (PCT) has been recently accepted as a marker for diagnosing infection. The aim of the present study was to determine whether PCT levels are associated with infection severity of diabetic foot ulcers and whether PCT levels would be helpful to differentiate infected diabetic foot ulcer (IDFU) from IDFU associated with other infectious diseases (IDFU + O). Methods: - This research was conducted in a Sardar Patel Medical College, Bikaner over the 2016 academic year. We prospectively included 95 diabetic patients hospitalized for IDFU. Infection severity of diabetic foot ulcers was graded according to the Infectious Diseases Society of America-International Working Group on the Diabetic Foot clinical classification of diabetic foot infection. Chest radiograph, urinalysis, urine microscopy, urine culture, and blood cultures (if fever was present) were performed for all patients to diagnose other infectious diseases. Laboratory parameters were measured from blood venous samples. Quantitative data from mid-year examination marks were analysed at the end of the academic year. Results: - PCT (0.286, P < 0.001) and C-reactive protein (0.368, P < 0.001) levels were significantly associated with infection severity of diabetic foot ulcers. However, only PCT levels could differentiate patients with associated infectious diseases from patients with no concomitant infection (area under the receiver-operator characteristic curve 0.729, P < 0.0001; cut-off value 0.44; sensitivity 88.7; specificity 70.2). Conclusion: -PCT and CRP levels positively correlated with infection severity of diabetic foot ulcers and PCT levels > 0.48 ng/mL in patients with IDFU may be associated with other systemic bacterial infection.